Tools for Urban Sustainability: Social Cartography for an Observatory on the City / Ferramentas de Sustentabilidade Urbana: Cartografia Social para um Observatório na Cidade - Restaino, Gabriella; Muniz dos Santos Filho, Antonio; Pessoa Lira Souza, Sofia; Lima Araujo, Luciana; Barbosa de Melo, Peterson (Revista de Direito da Cidade, 2021)
Abstract The study case intends to reconstruct the rules of the actual urban legislation on the Special Areas of Social Interest of a tropical Brazilian city, Maceió, capital of Alagoas State. Objective: to propose a new tool to support future urban plans, the Social Cartography, which takes into account the needs of the “forgotten” contemporary city, the city “in the shade”: the “self-built” settlements. The more significant of these, have historical origins, they are located in areas for the fishermen in the periphery of the city, areas that exists since colonial times. Others are located in areas of new contemporary occupation / “invasion”. Method: the study wants to investigate how the community is facing the new challenges of contemporary world. Results and Contributions: the outcomes of the research will be a propose to present in meetings with governing bodies and inhabitants, in order to identify practical and concrete solutions to existing problems of the trend in the construction of new modern buildings in total dis-harmony with the historical and contemporary landscape and in opposition of the traditional self-building areas. Also, can be to produce a new interest of the material and immaterial culture of the traditional areas: fishermen villages, contemporary poor districts and historical core of the city. Keywords: sustainable models and techniques; City Law; decision support system; Special Areas of Social Interest Resumo O estudo de caso pretende reconstruir as normas da atual legislação urbana sobre as Áreas Especiais de Interesse Social de uma cidade tropical brasileira, Maceió, capital do Estado de Alagoas. Objetivo: para propor uma nova ferramenta de apoio a futuros planos urbanísticos, a Cartografia Social, que leva em conta as necessidades da cidade contemporânea “esquecida”, a cidade “na sombra”: os assentamentos “autoconstruídos”. As mais significativas delas, de origem histórica, encontram-se em áreas de pescadores nas periferias da cidade, áreas que existiam desde a época colonial. Outros estão em áreas de nova ocupação / "invasão" contemporânea. Método: investigar como a comunidade está enfrentando os novos desafios do mundo contemporâneo. Resultados e Contribuições: resultados da investigação serão propostos para apresentação em reuniões com órgãos governamentais e moradores, de forma a identificar soluções práticas e concretas para os problemas existentes da tendência na construção de novos edifícios modernos em total desarmonia com o contexto paisagístico histórico e contemporâneo e em contraste com as áreas tradicionais de construção própria. Além disso, pode ser o de produzir um novo interesse na cultura tangível e intangível de áreas tradicionais: vilas de pescadores, bairros pobres contemporâneos e o núcleo histórico da cidade. Palavras-chave: modelos sustentáveis e técnicas sustentáveis; Direito da Cidade; sistema de apoio à decisão; Áreas especiais de interesse social.